2008
DOI: 10.1093/rheumatology/ken083
|View full text |Cite
|
Sign up to set email alerts
|

Messenger ribonucleic acid expression profile in peripheral blood cells from RA patients following treatment with an anti-TNF-α monoclonal antibody, infliximab

Abstract: Our results suggest that a customized low-density microarray is useful for monitoring mRNA expression profiles in peripheral blood cells, enabling us to identify a unique set of genes with differentially regulated expressions in responders and non-responders to a TNF inhibitor among patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 54 publications
3
49
0
2
Order By: Relevance
“…An interferon signature similar to SLE and myositis was identified in patients with scleroderma (98). Antiphospholipid syndrome was reported as a side effect in patients receiving IFN- therapy for unrelated diseases (101,102).…”
Section: Other Systemic Autoimmune Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…An interferon signature similar to SLE and myositis was identified in patients with scleroderma (98). Antiphospholipid syndrome was reported as a side effect in patients receiving IFN- therapy for unrelated diseases (101,102).…”
Section: Other Systemic Autoimmune Diseasesmentioning
confidence: 98%
“…In myositis, pDCs infiltrate tissues and might secrete aberrant amounts of IFN-I; ISGs are significantly upregulated in both inflamed muscles and PBMCs (96)(97)(98). Serum IFN- is correlated to serum muscle enzyme levels in untreated disease among patients with juvenile dermatomyositis and inversely correlated to the duration of untreated disease (99).…”
Section: Inflammatory Myositismentioning
confidence: 99%
“…The regulation of IFN-response genes by infliximab in RA turned out not to be as consistent as previously described for patients with SOJIA (Palucka et al, 2005), but varies between patients. A decrease in IFN-activity appears to be associated with good clinical responses (van Baarsen et al, 2010d;Sekiguchi et al, 2008). Koczan and colleagues reported that early downregulation of genes involved in different pathways and cellular processes such as TNF signalling via NFκB, NFκB-independent signalling via cAMP, and the regulation of cellular and oxidative stress response (e.g.…”
Section: Pharmacodynamics Of Tnf-blockadementioning
confidence: 99%
“…Ultimately, this may lead to apply therapy to each patient that is best suited for the patient, also called "personalized medicine". A number of studies focussed on the delineation of baseline differences in peripheral blood cells (whole blood and PBMC) with the purpose of predicting response (Lequerre et al2006;Koczan et al, 2008;Sekiguchi et al 2008;Tanino et al 2009;Julia et al, 2009a;Bienkoska et al, 2009;Van Baarsen et al, 2010c, 2010dStuhlmuller et al, 2010). The results of these studies made clear that identification of predictors in the blood compartment is not trivial.…”
Section: Prediction Of Response To Tnf Blockadementioning
confidence: 99%
“…In order to identify predictive factors for a given biological agent, genetic polymorphism 28,29 and comprehensive mRNA expression analysis 30,31 have been employed. Following this line, many investigators are extensively searching for predictive factors of ADRs, including infection 32 and infusion reactions of biologics.…”
Section: Future Perspectives For Biological Agents In Ra Treatmentmentioning
confidence: 99%